Financial Effects of the 2017 Tax Cuts and Jobs Act on Nonindustrial Private Forest Landowners: A Comparative Study for 10 Southern States of the United States. Issue 6 (11th August 2020) - Baral, Srijana; Li, Yanshu; Mei, Bin
Abstract: Changes in tax codes applicable to timberland investments can affect tax treatment of timber revenues and expenses. The 2017 Tax Cuts and Jobs Act (TCJA) is regarded as the most expansive overhaul of tax codes in the United States since 1986; however, our understanding of its effects on timberland investments for family forest owners has yet to be explored. Using the discounted cash-flow method, we estimated and compared effects of TCJA on land expectation value (LEV) and net tax from managing timberland for two classifications of median-income family forest owners in 10 southern states. Results showed a decrease in LEV and net tax for both material participants and investors, with a greater effect on landowners managing timberland as investments. Thus, owning timberland can become less beneficial under the current law for median-income family forest landowners. Study Implications: Family forests occupy a large portion of the total forest area in the United States and provide various goods and services to society. Taxes and tax policies are regarded as important issues for these landowners because policies could ultimately influence timberland investment, ownership structure, and management activities. After the 2017 tax reform, landowners became concerned about the effect of the new act on profitability and financial return from timberland investment. Here, we attempt to provide a better understanding of tax effects by estimating change in net benefit of owning and managing timberland under the current law compared with the previous law in 10 southern states. For policymakers, this study can provide insight into the importance of considering unique characteristics of timberland investment during the tax policy design and evaluation process. For landowners, this study can facilitate the timberland investment decisionmaking process and serve as a guide to the effects of the new tax rules on returns.